Pengaruh Experiential Marketing dan Emotional Branding Terhadap Loyalitas Pelanggan Melalui kepuasan Konsumen Starbucks di Surabaya - Farah Nabilla Azhar; Lia Nirawati (Universitas Batanghari, 2022)
This study aims to explain the effect of experiential marketing and emotional branding on customer loyalty at Starbucks Coffee Surabaya. This research collection technique uses an interview system and produces 240 samples with the criteria of Surabaya residents who have bought Starbucks Coffee at least once. This type of research is explanatory research. This data analysis technique uses SPSS. The results of the Sobel test state that the effect of mediation or intervention between marketing experience on customer loyalty through satisfaction, and the effect of mediation or intervention between emotional branding on customer loyalty through satisfaction.